Adaptations in Basal and Hypothalamic-Pituitary-Adrenal-Mediated Deoxycorticosterone Responses Following Ethanol Self-Administration in Cynomolgus Monkeys - Jimenez, Vanessa A.; Porcu, Patrizia; Morrow, Leslie; Grant, Kathleen (Frontiers in Endocrinology, 2017)
Acute ethanol activates the hypothalamic-pituitary-adrenal (HPA) axis, while long-term exposure results in a blunted neuroendocrine state, particularly with regards to the primary endpoint, cortisol, the primary glucocorticoid produced in the adrenal cortex. However, it is unknown if this dampened neuroendocrine status also influences other adrenocortical steroids. Plasma concentration of the mineralocorticoid and neuroactive steroid precursor deoxycorticosterone (DOC) are altered by pharmacological challenges of the HPA axis in cynomolgus monkeys. The present study investigated HPA axis regulation of circulating DOC concentration over the course of ethanol (4% w/v) induction and self-administration in non-human primates (Macaca fasciculata, n=10). Plasma DOC, measured by radioimmunoassay, was compared at baseline (ethanol naïve), during schedule-induced polydipsia, and following 6-months of 22 h/d access to ethanol and water. The schedule-induction of ethanol drinking did not alter basal DOC levels, but selectively dampened the DOC response to pharmacological challenges aimed at the anterior pituitary (ovine corticotrophin releasing hormone) and adrenal gland (post-dexamethasone ACTH), while pharmacological inhibition of central opioid receptors with naloxone greatly enhanced the DOC response during induction. Following 6-months of ethanol self-administration, basal DOC levels were increased more than 2 fold, while responses to each of the challenges normalized somewhat, but remained significantly different than baseline. These data show that HPA axis modulation of the neuroactive steroid precursor DOC is markedly altered by the schedule-induction of ethanol drinking and long-term voluntary ethanol self-administration. The consequences of chronic ethanol consumption on HPA axis regulation of DOC point towards allostatic modification of hypothalamic and adrenal function.